Implementation of the Rights and Obligations of the Parties in the Law of the Agreement - Rona Isrofani; Agus Apria Widodo; Alya Tsabita; Aidin Baharudin Yusuf (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The research method used is a literature study research system where research is carried out by searching, reading, recording, and analyzing findings in the field related to written sources such as books, journals, archives, articles, or magazines that correlate with the current problem studied. The Deed of Agreement corresponds to the Dutch term overeenkomst or English agreement. Hence, the term contract law. If the term engagement rights are intended to cover all forms of engagement in Volume 3 of the Civil Code, namely legal obligations originating from contracts and legal obligations made by law. This term applies only to contract law. The threat of such penalties from the guarantor of performance is required if the engagement is not fulfilled. With the promise of the threat of punishment, the creditor cannot be separated from the obligation to prove the magnitude of the loss he has suffered. Cancellation of the threat of punishment does not result in the cancellation of the principal engagement.